Waste management post consumption: a reverse logistics proposal for nail enamel - Thode Filho, Sergio; Sena, Marcelo Fonseca Monteiro de; Talhas, Isadora Bastos; Paiva, Julieta Laudelina; Marques, Mônica Regina da Costa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
n Brazil, you lose bristle 8 billion dollars per year in raw materials with potential for recovery/recycling, however waste such as glass, plastic, aluminum, paper, cardboard, are little used. Unlike other countries, in Brazil there is still no law providing for aselective collection to waste as the nail polish. Few private initiatives and there is no compensation from the government. Countries like France, USA, England, part of the nail polish to the category of hazardous household waste, and there are specific collections for such waste. Due to scarcity of scientific studies, mainly national, on the impacts associated with the improper disposal of nail polish, the data used for the preparation of the conceptual bases for the reverse logistics model were mainly derived from surveys conducted by Thode-Filho et al. (2014). Therefore, the proposition of reverse logistics model objectified in this current work is the qualitative and quantitative data from the city of Duque de Caxias, however can be understood and applied in a comparative way in any city in Brazil. This work demonstrated, albeit preliminarily, the existence of methodologies and mechanisms for mitigating the environmental impacts generated by enamel waste nails. However, stimuli are needed, public awareness and the development ofpublic policies to become effective what is presented and demonstrated theoretically.